Digestibility of Bacillus firmus K-1 pretreated rice straw by different commercial cellulase cocktails. Issue 5 (2nd May 2022) - Teeravivattanakit, Thitiporn; Baramee, Sirilak; Ketbot, Prattana; Waeonukul, Rattiya; Pason, Patthra; Tachaapaikoon, Chakrit; Ratanakhanokchai, Khanok; Phitsuwan, Paripok
Abstract: Removal of xylan in plant biomass is believed to increase cellulose hydrolysis by uncovering cellulose surfaces for cellulase adsorption and, in turn, catalysis reaction. Herein, we describe an eco-friendly method by culturing a xylanolytic Bacillus firmus K-1 on rice straw to remove xylan. The bacterium was grown on 2.5% ( w/v ) rice straw with different biomass particle sizes for two days at 37 °C. We found that the particle sizes ranged from <1 to 5 mm gave a similar xylan removal degree (about 21%). Besides, the porosity and disintegration of the rice straw fibers were observed at the molecular level. The digestibility of pretreated rice straw was tested with different commercial cellulase cocktails. We found that the pretreated rice straw was more susceptible to enzymatic hydrolysis, giving 30–70% glucan conversion than the untreated one. The degree of cellulose hydrolysis depended strongly on the kinds of enzyme and their formulations. Highlight: Culturing B. firmus K-1 on rice straw yielded about 21% removal of xylan. Particle sizes (of 1–5 mm) had negligible effects on xylan removal efficiency. The degree of glucan conversion in pretreated biomass relied on enzyme formulation.